Supervisi untuk Pengembangan Soft Skills Siswa Berbasis Kebutuhan Dunia Kerja - Kadevie, Sri Santi; Waruwu, Marinu; Halida, Halida; Enawaty, Eny (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This article discusses the importance of integrating soft skills in education to prepare students to face the challenges of the world of work. It is emphasized that effective supervision strategies, including collaborative supervision and constructive feedback, act as a catalyst in the development of soft skills. Additionally, implementing integrated approaches and active learning models, such as project-based learning, can increase student engagement. Holistic evaluation is needed to measure the development of students' soft skills. Although challenges exist, policy support and teacher training are essential to ensure the success of this integration, resulting in graduates who are competent and ready to face the future.